2014
DOI: 10.3109/0886022x.2014.990348
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of relationship between sexual functions, depression and quality of life in patients with chronic kidney disease at predialysis stage

Abstract: Aim: The relation of chronic kidney disease (CKD) with metabolic, psychiatric and endocrinologic disorder is well-known. Depressive mood and sexual dysfunction are frequently observed as renal functions deteriorate. We aimed to analyze the relationship of sexual dysfunction, depressive mood and life quality in patients with CKD at predialysis stage. Patients and methods: Fifty-three patients; 27 female and 26 male with CKD who had estimated glomerular filtration rate (eGFR) between 15 and 90 mL/min and followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 34 publications
1
24
1
4
Order By: Relevance
“…The present study investigated 205 male patients with diabetes, of which 70 (34.2%) patients had TT levels < 12 nmol/L. Among healthy male individuals, the reported percentage of individuals with sexual dysfunction varies between 20 and 80% [ 19 21 ]. In an Australian cross-sectional study of 1089 patients with type 2 diabetes, 36.5% patients had hypogonadism [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study investigated 205 male patients with diabetes, of which 70 (34.2%) patients had TT levels < 12 nmol/L. Among healthy male individuals, the reported percentage of individuals with sexual dysfunction varies between 20 and 80% [ 19 21 ]. In an Australian cross-sectional study of 1089 patients with type 2 diabetes, 36.5% patients had hypogonadism [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, effects of a decreased QoL due to SD on the course of CKD should not be underestimated. SD is a serious problem in all stages of CKD: predialysis, dialysis, and after renal transplantation [8,33,34].…”
Section: In Perspectivementioning
confidence: 99%
“…14 Hope can be a therapeutic, multi-dimensional, dynamic, and powerful factor, playing an important role in coping with disabilities. 15 Different studies have shown a positive association between hope and positive emotions 16 and self-respect. 17 Additionally, negative associations have been revealed between hope and exhaustion 18 and negative emotions.…”
Section: Introductionmentioning
confidence: 99%